The effect of mulching soil moisture retention: (A case study of the wooden plants’ area) - Gankhuyag, Elbegzaya; Ganbat, Byambaa; Sodnomtsog, Bumnanjid (Mongolian Journal of Geography and Geoecology, 2022)
This study was conducted with the aim of comparing stone and leaf mulch for soil moisture protection, detecting how soil moisture dynamics change due to precipitation and air temperature, and then using the results for further research. In the study, measurements were made with a HOBO H21-002 model TDR data logger and a S-SMC-M005 model moisture meter. Soil moisture measuring sensors were installed at 5 and 30 cm depths, and measurements were taken every hour from June to October 2022 (for four months). Compared to the control area, the average amount of total moisture at the depth of 5 cm of the soil was 15.73% of the leaf mulch and 25.64% of the stone mulch. However, compared to the control area, the soil moisture in the 30 cm depth was 2.18% of the leaf mulch and 5.58% of the stone mulch. Tree height growth was greater in the stone mulch area for three months and 2.7% greater than in the control area. According to our research, during the period of measurement, the stone mulch area was the area that retains moisture better for a long time by penetrating moisture to the soil 30 cm deep. Хөрсний чийг хамгаалах судалгааны дүнгээс ХУРААНГУЙ Хөрсний чийг хамгаалах чулуу болон навчин хучаасыг харьцуулан судалж, хур тунадас, агаарын температурын нөлөөгөөр хөрсний чийгийн динамик хэрхэн өөрчлөгдөж буйг илрүүлж, үр дүнг цаашдын судалгааны ажилд ашиглах зорилготойгоор энэхүү судалгааг хийлээ. Судалгаанд HOBO Н21-002 загварын ТDR дата логгероор S-SMC-M005 загварын чийг хэмжигч ашиглан хэмжсэн. Хөрсний чийг хэмжих мэдрэгчүүдийг 5, 30 см гүнүүдэд суулган нэг цагийн давтамжтайгаар 2022 оны VI сараас эхлэн X сарын хооронд (дөрвөн сарын турш) хэмжилт хийсэн. Хөрсний 5 см гүнд нийт чийгийн дундаж хэмжээ хяналтын талбайтай харьцуулахад навчин хучаас 15.73%, чулуун хучаас 25.64%-ийн чийгтэй байна. Харин хөрсний 30 см гүнд чийгийг хяналтын талбайтай харьцуулахад навчин хучаас 2.18%, чулуун хучаас 5.58%-ийн чийгтэй байна. Гурван сарын хугацаанд чулуун хучаастай талбайн модны өндрийн өсөлт илүү байсан ба хяналтын талбайгаас 2.7%-иар илүү байна. Хэмжилт хийсэн хугацаанд чулуун хучаастай талбай чийгийг илүү сайн барьж хөрснийхөө 30 см-ийн гүн рүү чийгийг нэвчүүлж урт хугацаандаа чийгийг хадгалж байсан. Түлхүүр үг: Хөрсний чийг, Навчин хучаас, Чулуун хучаас